Emergency and urgent care systems in Australia, Denmark, England, France, Germany and the Netherlands – Analyzing organization, payment and reforms. Issue 1 (January 2019) - Baier, Natalie; Geissler, Alexander; Bech, Mickael; Bernstein, David; Cowling, Thomas E.; Jackson, Terri; van Manen, Johan; Rudkjøbing, Andreas; Quentin, Wilm
Highlights: Several developed countries are reforming their emergency and urgent care system. Urgent primary care is expanded and increasingly centralized as in the Netherlands. Emergency and urgent primary care are increasingly coordinated e.g. in France. Several countries have concentrated emergency care provision at fewer hospitals. Abstract: Introduction: Increasing numbers of hospital emergency department (ED) visits pose a challenge to health systems in many countries. This paper aims to examine emergency and urgent care systems, in six countries and to identify reform trends in response to current challenges. Methods: Based on a literature review, six countries – Australia, Denmark, England, France, Germany and the Netherlands – were selected for analysis. Information was collected using a standardized questionnaire that was completed by national experts. These experts reviewed relevant policy documents and provided information on (1) the organization and planning of emergency and urgent care, (2) payment systems for EDs and urgent primary care providers, and (3) reform initiatives. Results: In the six countries four main reform approaches could be identified: (a) extending the availability of urgent primary care, (b) concentrating and centralizing the provision of urgent primary care, (c) improving coordination between urgent primary care and emergency care, and (d) concentrating emergency care provision at fewer institutions. The design of payment systems for urgent primary care and for emergency care is often aligned to support these reforms. Conclusion: Better guidance of patients and a reconfiguration of emergency and urgent care are the most important measures taken to address the current challenges. Nationwide planning of all emergency care providers, closely coordinated reforms and informing patients can support future reforms.